Balancing Contracts: The Crucial Role of Pre-contractual Disclosure in Technical Assistance Agreements - Alwan , Ali Hasan (Indonesian Journal of Law and Economics Review, 2023)
This study rigorously delineates the imperative of pre-contractual disclosure in technical assistance contracts, spotlighting the legal necessity for suppliers to provide indispensable technical information vital for efficient recipient resource utilization. Emphasizing informed consent and mutual satisfaction, this pre-contractual mandate, rooted in the principle of good faith, addresses negotiation power imbalances. It clarifies that meeting this obligation differs from mere due diligence, demanding a specific outcome prior to contract formation. It asserts that debtors must be apprised of negotiated data unbeknownst to the creditor, justifiably. The ramifications are dual: rectifying power differentials and ensuring parity in knowledge among contracting parties. The study aims to enrich legislative frameworks for party protection, utilizing qualitative methods for definition and analysis. Results shed light on the nuanced aspects of pre-contractual disclosure, impacting contractual rebalancing and knowledge equality. This research advocates global attention to legislative actions promoting transparency and fairness in technical assistance agreements. Highlights : Clarifies the Legal Imperative: The study meticulously defines the legal obligation for suppliers to disclose crucial technical information in technical assistance contracts, ensuring informed consent. Addresses Power Imbalances: Emphasizes the role of the principle of good faith in rectifying negotiation power imbalances, contributing to more equitable contractual relationships. Global Advocacy for Legislative Measures: Calls for international attention to legislative actions fostering transparency and fairness in technical assistance agreements. Keywords : Pre-contractual Disclosure, Technical Assistance Contracts, Informed Consent, Good Faith, Legislative Regulation